An Integrated Method for Wind Power Estimation: Application for West Cyprus Areas - Kastanas, Ioannis (Department of Civil Engineering and Geomatics, Faculty of Engineering and Technology, Cyprus University of Technology, 2013)
The motivation of this study was to explore the possibility of estimating the wind energy potential at several areas in order to cover the western part of the island with the respective information. The methodology of the analysis was based on a standard application program, WAsP. Monthly wind speed and direction statistics (on a bi – daily basis, every 12 hours) for six stations from 2001 – 2008, show a strong influence of sea – breeze, which is very intense, especially in the southern coast of the island. In the case of the northern coast (Polis station and Kato Pyrgos), the wind speed remains relatively high also during the night, exhibiting much lower daily variation, although still changing its variation. The wind statistics obtained here, served as the basis in order to estimate corrected statistical distributions over the extended areas of application through Wind Atlas Analysis and Application Program (WAsP) which modifies the wind flow due to local topographic effects. Aggregation of the data with statistical weighting methods, allowed the extrapolation of the results and the visualization over the western part of the island. It appears that coastal areas are affected by local flows of sea breeze that is dependent by the succession of land and sea. Mean wind speed values at stations of Limassol and Mallia range to 2 – 5m/s, at Pafos about 5m/s, at Prodromos at 3 – 4m/s, at Kato Pyrgos at 2.5m/s – 3m/s, and at Polis at 3m/s. The application indicates that interesting points with higher wind energy potential, suitable for wind resource exploitable exist. The wind potential analysis through WAsP showed that all areas are influenced significantly by the complex orography model and the wind speed easily reaches the value of 10m/s. However, further application and inclusion of all the data available from nearby stations is needed in order to improve the accuracy and complete the coverage of the island. The particular methodological framework applied and the results obtained can be utilized by potential investors and wind energy developers.
Keywords: WAsP; Wind Atlas Analysis and Application Program